A public health approach to eating disorders prevention: It's time for public health professionals to take a seat at the table - Austin S (BMC, 2012)
Abstract Background The societal burden of eating disorders is clear, and though there is a compelling need for a public health approach to eating disorders prevention, public health professionals have yet to take up the challenge. Discussion The article lays out an argument for what steps need to be taken to bring a public health approach to eating disorders prevention. First, stock is taken of what the field has achieved so far, using tools from the prevention science literature, and, second, a research plan of action is offered that plays to the unique strengths of public health, drawing on a triggers-to-action framework from public health law. Minimal participation was found from public health professionals in eating disorders prevention research, and the vast majority of prevention research to date was found to be concentrated within the disciplines of psychology and psychiatry. Extreme disciplinary concentration of the research has led to a preponderance of individually targeted prevention strategies with little research focused on environmental targets, particularly at the macro level. New environmental initiatives are now emerging, such as a government-sponsored mass media anti-dieting campaign, and legal bans on extremely thin models in advertising, but for the most part, they have yet to be evaluated. A triggers-to-action framework, which focuses on evidentiary base, practical considerations, and political will, developed in public health law provides a basis for a strategic research plan for a public health approach to eating disorders prevention. Summary There is enormous potential for growth in the scope and diversity of eating disorder prevention research strategies, particularly those targeting the macro environment. A public health approach will require a strategic plan for research that leverages the macro environment for prevention. The full engagement of public health professionals will bring to the field the much broader range of preventive strategies and perspectives needed to tackle the problem of eating disorders.